Sosialisasi Digital Marketing Melalui Media Sosial, Marketplace, dan Iklan Online di Kelurahan Paria - Agus Purwanto; Andi Sumangelipu; Esse Yuliani; Andi Dian Panca Lestari; Muh. Sholihuddin Prisdan (YP-SDI Lamaddukelleng, 2025)
Marketplaces have become an integral part of the digital marketing ecosystem. Digital marketing offers various benefits for village and sub-district communities, one of which is increased market access. By using digital platforms, local products can be marketed not only locally but also nationally and internationally. According to a survey by Google and Temasek, the e-commerce market in Indonesia is estimated to reach USD 82 billion by 2025, demonstrating the enormous potential for local products (Google, Temasek, 2020). According to a report from the United Nations Development Programme (UNDP), improving digital literacy in rural areas can increase community participation in the digital economy and accelerate local economic growth (UNDP, 2021). Therefore, digital marketing training programs must be integrated into village and sub-district development programs. To address this need, as a form of community service, digital marketing outreach was conducted through social media, marketplaces, and online advertising in Paria Village, Majauleng District, Wajo Regency. This community service aimed to increase the knowledge and understanding of sub-district residents regarding digital marketing in boosting local economic growth. Overall, this digital marketing outreach offers significant opportunities for rural communities to improve their economic well-being. With a good understanding and the right support, rural communities can leverage digital platforms to expand their market reach and increase their income.